2015
DOI: 10.1074/jbc.m114.615088
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mRNA Fate Modulators Dhh1 and Pat1 in TNRC6-dependent Gene Silencing Recapitulated in Yeast

Abstract: Background: Animal microRNAs silence their target mRNAs by promoting mRNA degradation and inhibiting translation via GW182/TNRC6. Results: TNRC6 induces silencing effects in S. cerevisiae via CCR4-NOT complex and Dhh1-Pat1 when tethered to reporter mRNAs. Conclusion: TNRC6 utilizes the conserved mRNA fate modulators for gene silencing in yeast. Significance: Yeast genetic tools are now available to study intricate actions of TNRC6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
(106 reference statements)
1
10
0
Order By: Relevance
“…Consistent with this observation, previous studies reported differential contributions of Dcp2 and Cnot7 to miR‐430‐mediated degradation of some mRNAs (Makino et al . ). These results indicate that each maternal mRNA differentially depends on Cnot7‐mediated deadenylation and Dcp2‐mediated decapping for degradation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Consistent with this observation, previous studies reported differential contributions of Dcp2 and Cnot7 to miR‐430‐mediated degradation of some mRNAs (Makino et al . ). These results indicate that each maternal mRNA differentially depends on Cnot7‐mediated deadenylation and Dcp2‐mediated decapping for degradation.…”
Section: Resultsmentioning
confidence: 97%
“…To analyze the contribution of Dcp2-mediated decapping to maternal mRNA clearance, we inhibited Dcp2 function in zebrafish embryos by over-expressing a dominant-negative form of zebrafish Dcp2 that contained mutations in its catalytic residues (van Dijk et al 2002;Makino et al 2015) (Fig. 1A, called Dcp2dominant negative (Dcp2-DN) hereafter).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that 4E-T promotes miRNA-mediated mRNA decay through the eIF4E-binding domain, suggesting that 4E-T bridges the 3 0 -terminal mRNA decay complex to the 5 0 m 7 G-cap via binding to eIF4E [55]. Given that RISC can induce decapping and subsequent decay of target mRNAs with the internalized poly(A) tail or target mRNAs lacking poly(A) tail [53,54], decapping is not merely a consequence of miRNA-mediated deadenylation but it can be induced in a deadenylationindependent manner. However, deadenylation normally precedes mRNA decay in mammalian Figure 1.…”
Section: Mechanism Of Mirna-mediated Mrna Decay In Animalsmentioning
confidence: 97%
“…For more details on the structural bases for the interactions between GW182 and its interactors, see Jonas and Izaurralde [143]. decay by recruiting decapping factors onto the target mRNAs [53][54][55]. In mammalian cells, the catalytic subunit of decapping complex (DCP2), and decapping activators DCP1, RCK/p54/ DDX6 (also known as Dhh1 in yeast, Me31B in Drosophila melanogaster, and Xp54 in Xenopus) and EDC4 (also known as Ge-1 or Hedls) coimmunoprecipitated with Ago proteins [56][57][58][59].…”
Section: Mechanism Of Mirna-mediated Mrna Decay In Animalsmentioning
confidence: 99%